2011
DOI: 10.1021/bi201381e
|View full text |Cite
|
Sign up to set email alerts
|

Conformational Flexibility in the Allosteric Regulation of Human UDP-α-d-Glucose 6-Dehydrogenase

Abstract: UDP-α-D-xylose (UDX) acts as a feedback inhibitor of human UDP-α-D-glucose 6-dehydrogenase (hUGDH) by activating an unusual allosteric switch, the Thr131 loop. UDX binding induces the Thr131 loop to translate ~5 Å through the protein core, changing packing interactions and rotating a helix (α6(136-144)) to favor the formation of an inactive hexameric complex. But how does to conformational change occur given the steric packing constraints of the protein core? To answer this question, we deleted Val132 from the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
101
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(106 citation statements)
references
References 40 publications
5
101
0
Order By: Relevance
“…4). As a control, we generated an additional point mutant, ⌬132, in which valine 132 was deleted and which had been reported to be exclusively hexameric (25). Consistent with the prior results, this mutant had undetectable activity (Table 1) and eluted at the molecular mass of the hexamer irrespective of substrate or cofactor addition.…”
Section: Ugdh Quaternary Structure Disrupted By Mutagenesis Of Thr-32supporting
confidence: 76%
See 2 more Smart Citations
“…4). As a control, we generated an additional point mutant, ⌬132, in which valine 132 was deleted and which had been reported to be exclusively hexameric (25). Consistent with the prior results, this mutant had undetectable activity (Table 1) and eluted at the molecular mass of the hexamer irrespective of substrate or cofactor addition.…”
Section: Ugdh Quaternary Structure Disrupted By Mutagenesis Of Thr-32supporting
confidence: 76%
“…Several reports have provided structural and enzymologic insights into UGDH function in multiple species (6,7,10,11,(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26). In all cases the enzyme oxidizes UDP-glucose through two NAD ϩ -dependent electron transfers.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…UDP-Xyl binding stabilizes the E Ω conformation of hUGDH (Figure 1) 1618 . Competition with UDP-Glc induces the low substrate affinity E Ω conformation of hUGDH to undergo a cooperative conformational change to the high affinity E state 16, 39 .…”
Section: Resultsmentioning
confidence: 99%
“…We previously generated an obligatory homodimeric point mutant of hUGDH, T325D, in which interactions at the dimer-dimer interface were disrupted to show that the enzyme retained only ≈20% of wild-type activity in this state and lacked the ability to contribute significant UDP-glucuronate to downstream products 13 . However, an obligate hexamer caused by a single amino acid deletion, Δ132, also showed no detectable activity 13, 14 . Moreover, crystal structure determination and sedimentation velocity characterization have shown that an endogenous inhibitor of UGDH, UDP-xylose, functions by binding within the UDP-glucose active site and altering subunit association to yield an inactivated hexamer 15, 16 .…”
mentioning
confidence: 99%